A Novel Direct‐Current Piezoelectric Energy Harvester with Sustainable Output. Issue 1 (7th December 2022) - Liu, Lei; He, Lipeng; Hu, Dianbin; Hu, Renhui; Sun, Baoyu; Tian, Xiaochao
Abstract : The crest factor is an important indicator to measure the performance of the load. To reduce the crest factor of the system and improve the internal stability of the circuit, this article proposes a novel direct‐current piezoelectric energy harvester with sustainable output (S‐PEH). Voltage superposition with phase coupling could significantly improve the stability of the circuit system and reduce the interference and damage of transient pulses to the system. Here, the influence of angle size and phase number on the output performance of S‐PEH is studied. S‐PEH could produce a more stable voltage output with a low crest factor through phase coupling. At 3 P 120°, the optimum MAX voltage and root mean square (RMS) voltage are 29.06 and 16.55 V. The maximum RMS power is 1.38 mW. When the rotating speed is 550 r min −1, the lowest crest factor is 1.35. The charging rate is four times higher than a single‐group piezoelectric patch. Experiments show that S‐PEH can make light‐emitting diodes (LEDs) and calculators work stably. These results show that S‐PEH has great prospects in the power supply of wireless sensor networks and microelectronic devices. Abstract : Here, a novel direct‐current piezoelectric energy harvester with sustainable output (S‐PEH) is proposed. The maximum root mean square (RMS) power is 1.38 mW. When the rotating speed is 550 r min −1, the lowest crest factor is 1.35.